Renal intravascular lymphoma in a dog - Renata Dalcol Mazaro; Rafael Almeida Fighera; Flávia Serena da Luz; Alana Pivoto Herbichi (Ciência Rural)
ABSTRACT: A 10-year-old male large mixed breed dog was presented with skin ulcers and fracture on the right hind limb caused by vehicle collision. Given required limb amputation, and as being a shelter senior dog, euthanasia was requested by the owner and a complete post-mortem examination was conducted immediately after death. Gross changes were consistent with marked bilateral nephromegaly. Histopathological examination of the kidneys revealed round cells filling blood vessels. Immunohistochemically, the round cells were positive for CD3 antibody. Based on these findings, in absence of involvement of the bone marrow and peripheral blood, and inexistence of primary extravascular masses, the tumor was classified as T-cell intravascular lymphoma. To the author’s knowledge, this is the first report describing intravascular lymphoma involving the kidneys alone in a dog.